Legacy and impact of the 1925 Geneva Protocol: one hundred years of treaties and debates on chemical and biological weapons - Grunden, Walter E.; Tuovinen, Olli H. (Frontiers in Microbiology, 2025)
This essay examines the legacy and impact of the 1925 Geneva Protocol, which prohibited the use of chemical and biological weapons. This multinational treaty was an important milestone in the history of the non-proliferation of weapons of mass destruction concluded in the wake of the horror engendered by the use of poison gases in World War I. However, the 1925 protocol did not address the issues of verification, manufacturing, stockpiling, and transferring products of chemical and biological weapons or production technologies. A second treaty, the result of the Biological Weapons Convention of 1972, was concluded to address these issues. Despite the apparent success of prohibiting large-scale and widespread use of chemical and biological weapons, violations have occurred, nonetheless, and the treaties remain problematic in numerous ways. The centennial of this historic 1925 agreement and its successor treaties presents an opportunity for reflection upon their efficacy. Given that there have been “limited” episodes of chemical and biological warfare since that time, how can these events be explained in light of the protocol’s prohibitions? This essay argues that the 1925 Geneva Protocol has a mixed legacy and, at best, can be deemed only a qualified success. Other factors, such as political deterrence, scientific and technological limitations, and the problematic nature of these types of weapons may account for the absence of their mass use. The essay aims to serve as an introduction to the historiographical literature with an emphasis on biological weapons and the Geneva Protocol and includes tables as reference guides concerning the types of weaponized pathogens and toxins in question.